The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.1039/d2tc00486k
|View full text |Cite
|
Sign up to set email alerts
|

Inherent electron and hole trapping in amorphous phase-change memory materials: Ge2Sb2Te5

Abstract: When the amorphous state of a chalcogenide phase-change material is formed inside an electronic-memory device via Joule heating, caused by an applied voltage pulse, it is in the presence of...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
22
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(22 citation statements)
references
References 69 publications
0
22
0
Order By: Relevance
“…This is presumably due to the high interfacial energy and the formation of internal electron-hole traps within the bimetallic NPs, which, in turn, indicates the higher chemical stability of AgPt NPs over the monometallic Ag NPs, which restricts the release of ions into the solution during the reaction. 73 Dong's group reported that NiPd showed multienzyme activity and is employed for the colorimetric detection of glucose. NiPd hNPs had a hollow nanostructure, which provided an enhanced surface area with exposed active sites for the catalytic reaction of the nanozyme for the active adsorption and trapping of substrate molecules including TMB and H 2 O 2 in the hollow NPs that lead to a high catalytic efficiency of NiPd hNPs as well.…”
Section: Metals and Metal Oxidesmentioning
confidence: 99%
“…This is presumably due to the high interfacial energy and the formation of internal electron-hole traps within the bimetallic NPs, which, in turn, indicates the higher chemical stability of AgPt NPs over the monometallic Ag NPs, which restricts the release of ions into the solution during the reaction. 73 Dong's group reported that NiPd showed multienzyme activity and is employed for the colorimetric detection of glucose. NiPd hNPs had a hollow nanostructure, which provided an enhanced surface area with exposed active sites for the catalytic reaction of the nanozyme for the active adsorption and trapping of substrate molecules including TMB and H 2 O 2 in the hollow NPs that lead to a high catalytic efficiency of NiPd hNPs as well.…”
Section: Metals and Metal Oxidesmentioning
confidence: 99%
“…[16][17][18][19][20][21] The intrinsic charge-trapping processes at the localized electronic states of the amorphous material have also been considered as an alternative (electronic) explanation of the resistance drift. [22][23][24] Atomistic simulations have reported the existence of several localized unoccupied and occupied electronic states in the vicinity of the bandgap in amorphous phase-change materials. Zipoli et al associated the localization of defects in the bandgap of models of glassy GeTe with clusters of Ge atoms, in which at least one Ge atom is over-or undercoordinated.…”
mentioning
confidence: 99%
“…[27] Recently, we also showed that spontaneous electron-and holetrapping events are energetically favorable at the conduction-and valence-band edges in amorphous Ge 2 Sb 2 Te 5 . [24] One-electron traps produce deep occupied states in the bandgap, located in close proximity to the top of the valence band, while one-hole traps lead to the creation of unoccupied states around midgap. [24] The intrinsic defective-octahedral Ge and Sb sites inside the amorphous Ge 2 Sb 2 Te 5 network have been found to be responsible for the charge trapping.…”
mentioning
confidence: 99%
See 2 more Smart Citations